(untitled) (Sciences & Technologie. B, Sciences de l’ingénieur, 2007)
In this paper, we present a static response of a square or rectangular silicon membrane under uniform and constant pressure, in the case of weak perturbations. We employ Galerkin method with trigonometrical basis functions to provide an accuracy and simple solution w(x,y) for the silicon membrane. We then investigated a piezoresistive pressure sensor that have a silicon diaphragm with rectangular or square shape and employ piezoresistives gages. These gages are linked together in the form of Wheatstone bridge. The gages factor (K), sensitivity (Sp) and output voltage (ΔV) is analysed. The results obtained show that the change of resistance due to pressure was linear over a pressure range of [0 to 10bar]